Review of Polish contribution to snow cover research (1880–2017) - Falarz, Małgorzata; Nowosad, Marek; Bednorz, Ewa; Rasmus, Sipra (Quaestiones Geographicae, 2018)
The purpose of this article is to present the development of multifaceted research on snow cover conducted by Polish researchers in various parts of the world since the end of the 19th century up to the modern times. The paper describes Polish studies on physical and chemical properties of snow cover, its long-term changes, relationships between snow cover and climate, impact of snow cover on environmental conditions and human activity. This work is also an attempt to show the contribution of Polish snow-related research to the international achievements in this fields.